111k views
2 votes
Ax-bx+y=z solve for x​

User Eudore
by
5.4k points

2 Answers

3 votes


\bold{Answer}


\boxed{\bold{x=(z-y)/(A-b);\quad \:A\\e \:b}}


\bold{Explanation}


  • \bold{Solve: \ Ax-bx+y=z}


\bold{-------------------}


  • \bold{Subtract \ Y \ From \ Both \ Sides}


\bold{Ax-bx+y-y=z-y}


  • \bold{Simplify}


\bold{Ax-bx=z-y}


  • \bold{Factor \ Ax-bx: \ x\left(A-b\right)}


\bold{x\left(A-b\right)=z-y}


  • \bold{Divide \ Both \ Sides \ By \ A-b;\quad \:A\\e \:b}


\bold{(x\left(A-b\right))/(A-b)=(z)/(A-b)-(y)/(A-b);\quad \:A\\e \:b}


  • \bold{Simplify}


\bold{(x\left(A-b\right))/(A-b)=(z)/(A-b)-(y)/(A-b);\quad \:A\\e \:b}


\boxed{\bold{Eclipsed}}

User Keso
by
5.1k points
3 votes

Answer:

This question requires us to change the subject of a formula. This can be achieved by following the order of operations in reverse. First, isolate the terms with our variable of interest, x:

ax - bx = z - y

Then, we take x out as it is being multiplied to both a and b:

x(a - b) = z - y

Dividing (a - b) on both sides, we get:

x = (z - y) / (a - b)

Thus, the answer is x= z-y/a-b

Explanation:

User Cucko
by
4.6k points